PENGARUH TEKANAN, KEEFEKTIFAN SISTEM PENGENDALIAN INTERNAL, DAN BUDAYA ETIS MANAJEMEN TERHADAP KECURANGAN (FRAUD) PADA PENGELOLAAN DANA DESA - Ni Putu Ayu Mirah Anggrima Wati; Ni Wayan Yuniasih (Hita Akuntansi dan Keuangan, 2021)
Fraudx is an act of fraud that can harm other parties in order to obtain personal gain. Thisx study aims to determine the influence of pressure, the effectiveness of internal control systems, and the ethical culture of management against fraud in the management of village funds (empirical studies on villages in West Denpasar District). The population in this study was all village devices in villages in West Denpasar Sub-District, respondents used in this study as many as 64 people consisting of village heads, village secretaries, head of government, head of public welfare, head of service, head of finance, head of general and planning. Sample determination method using purposive sampling technique From the results of this study, the pressure has a positive and significant effect on fraud on the management of village funds. While the effectiveness of internal control system and ethical culture of management has no significant effect on fraud in village fund management.